Tailoring critical Al concentration to form external Al2O3 scale on Ni–Al alloys by computational approach. Issue 12 (1st September 2022) - Ross, Austin; Shang, Shun‐Li; Fang, Huazhi; Lindwall, Greta; Liu, Xuan L.; Zhao, Wei; Gleeson, Brian; Gao, Michael C.; Liu, Zi‐Kui
Abstract: Nickel (Ni)‐based superalloys for high‐temperature applications are often designed to form a continuous and slow‐growing oxide scale by adding Al and Cr and other beneficial elements. In the present work, the critical Al concentration in Ni–Al alloys needed to establish an α‐Al2 O3 scale in contrast to internal oxide formation is predicted as a function of temperature by means of the CALPHAD approach coupled with models in the literature, which account for the thermodynamics and kinetics of oxidation. The present thermodynamic remodeling of the Ni–O system results in a better agreement with experimental data of oxygen solubility in Ni at high temperatures. The oxygen solubility is combined with kinetic parameters to determine oxygen permeability in Ni, and the critical Al concentration needed to establish an α‐Al2 O3 scale at a given exposure temperature. Good agreement is found with available experimental data for both oxygen permeability and critical Al concentration, indicating the capacity of the CALPHAD approach to tailor oxidation resistance for materials of interest using thermodynamic and kinetic knowledge. Abstract : Graphical Abstract: Schematic representation of oxidation and critical Al concentration to form external Al2 O3 scale in the Ni–Al alloy system.